Excessive Borrowing in Debt Policy of the Russian Federation - O. G. Dmitrieva (Финансы: теория и практика, 2024)
The subject of the study is the debt policy of the Russian Federation in 2001–2023, the replenishment and withdrawal of the National Wealth Fund (NWF), the mechanism of the “fiscal rule”.   The purpose of the study is to discover the real effects of implementation of the fiscal mechanism known as “fiscal rule” as well as evaluation of the real efficiency and potential of the application of the mechanism of NWF as a countercyclical regulation tool.   The research used the method of system analysis of the federal budget data, budget balances in the framework of debt policy. The study also used the methodology for calculating excessive borrowings developed by the author for the first time. The scientific novelty of the study lies in the fact, which is discovered for the first time, that the increase of the state debt significantly exceeded the real requirement for state borrowings in order to cover the federal budget deficit. Special attention was paid to the budget surplus and the quantitative analysis of the state debt growth in the framework of surplus budgets. The research of a deficit-surplus budget phenomenon, initially described by O. Dmitrieva, is continued in the paper. The cost estimation of the excessive borrowings through the period of 2001–2023 is made. It has been established that the replenishment of the NWF according to the different versions of the “fiscal rule” is the main factor of the excessiveborrowings and, consequently, the increasing debt service costs. The share of debt service costs in the federal budget expenses increased from 1.8 % in 2009 to 5.33 % in 2023. It has been shown that the systemic vices in the section “sources of the budget deficit coverage” creates the opportunity for artificial increase in debt beyond the level of the real requirement for state borrowings, contributing to the state debt growth. In the conclusion of the research it is articulated that the NWF does not work and cannot work as a countercyclical regulation tool and an attempt to use it in this capacity leads to an increase in state debt and debt service costs. The practical significance of the research lies in the debt police improvement proposals and recommendations for budget classification and have the remarkable practical significance for all countries which have been creating national sovereign funds.